Research Brief One-Sheet No.2: Off-Duty Crime by Police Officers - Freiburger, Tina L (2012)
Virtually all of the existing data on the off-duty misconduct of police officers describes the misbehavior of New York Police Department (NYPD) officers (see e.g. Fyfe and Kane, 2006; Kane and White, 2009). These data indicate that a significant portion of police misconduct emanates from behavior that occurs off-duty, including domestic violence, bar fights, drunk driving, burglary, and sex offenses. The NYPD data are agency-specific however; so very little is known about the nature and character of off-duty misconduct perpetrated by police employed by other police agencies. The purpose of this study is to explore off-duty police crime in the United States through content analyses of news articles on arrested off-duty police officers. The study presents data on the arrested off-duty officers and case outcomes including legal and/or employment dispositions